"Act thin, stay thin": Commercialization, behavior modification, and group weight control. Issue 4 (2nd September 2019) - Parr, Jessica
Abstract: In 1968, Weight Watchers International introduced behavior modification practices to their established commercial program. At the time, the addition of behavioral psychology gave Weight Watchers a distinct advantage over the many competing weight control groups in postwar America. The process of combining group therapy with a controlled diet plan, behavior techniques and later, exercise, has significantly influenced American popular culture. This article considers how the commercialization of group weight control impacted the development and dissemination of a new multidimensional approach for weight management and how this has shaped popular ideas associated with dieting and wider understandings of healthy living.